Explicating individual training decisions - Walter, Marcel [Verfasser]; Müller, Normann [Verfasser] (My University, 2015)
"In this paper, we explicate individual training decisions. For this purpose, we propose a framework based on instrumentality theory, a psychological theory of motivation that has frequently been applied to individual occupational behavior. To test this framework, we employ novel German individual data and estimate the effect of subjective expected utility (SEU) from continuing vocational training (CVT), the effect of restricting factors, and the effect of personal characteristics on the willingness to pay for CVT. Our results imply that SEU is generally the main driver of training decisions. In contrast, financial restrictions are most decisive for persons who are more likely to participate in training (i.e., training tendency). Time restraints also help explain why some individuals are entirely unwilling to participate. Moreover, regional infrastructure is a crucial training determinant. We also find that age and vocational qualifications do not directly affect training decisions. However, persons in specific occupational settings (e.g., low occupational status, overly challenging workplace situations) do exhibit a lower training tendency. Additionally, the training behavior of these persons appears to be more rigid, making them less likely to react to changes in their cognitive attitudes to training." (Authors' abstract, BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 4 Kosten & Finanzierung; Berufliche Weiterbildung; Weiterbildungsbeteiligung; Einflussfaktor; Persönlichkeitsmerkmal; Weiterbildungskosten; Empirische Untersuchung